Caring for Pregnant and Postpartum Athletes: Athletic Trainers, Strength Coaches, and Athletic Coaches - Aly Matejka; Stephanie Born (Bowling Green State University, 2022)
OBJECTIVE: A survey was created to assess the experience, education, and self-perceived competence of treating and/or training pregnant and postpartum athletes among athletic trainers, strength coaches, and coaches.